The Materialist dialectic: Principles, dialogues and research in Education - De Melo, Alessandro [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2023)
It is intended, in this article, to produce a theoretical analysis, through bibliographic research, on the foundations of the materialist dialectic, assuming that this debate directly impacts the production of knowledge in the field of research in Education, in general, and in the field of Education Policies, in particular. The approach begins with the resumption of dialectics as a concept and in the ancient and modern conceptions, passing through the study of Hegel's idealist dialectic, to serve as a counterpoint to build the concept of dialectics in the Marxist tradition, contemplating a diversity of perspectives of this field. It is concluded with a synthesis of how research in Education Policies can benefit from the study of materialist dialectics.
La dialéctica materialista: principios, diálogos e investigación en Educación
A dialética materialista: princípios, diálogos e pesquisa em Educação
Keywords: Contradiction and overdetermination; Materialist dialectics; Research in Education; Research in Education Policies